ax+xm=z

Simple and best practice solution for ax+xm=z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for ax+xm=z equation:


Simplifying
ax + xm = z

Solving
ax + mx = z

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-1mx' to each side of the equation.
ax + mx + -1mx = -1mx + z

Combine like terms: mx + -1mx = 0
ax + 0 = -1mx + z
ax = -1mx + z

Divide each side by 'x'.
a = -1m + x-1z

Simplifying
a = -1m + x-1z

See similar equations:

| -2+4=12 | | x+y=390 | | 4-3+2(0-1)= | | 72=6(x-1) | | 2(3x-y)=84 | | 1.67x+11=2(x+2) | | 2x+7+(3-4)i=4+6i | | 2y-2=12y-13 | | -5-2y=6-6y | | 2x-7/3=11 | | 6x^4/3 | | 15w-60=-12w-35 | | -2/3x+3(5x+40)=-34 | | 2(3x-2)=84 | | 7x-3=-19+3x | | 110+7x= | | 2/(q-1)=3/(q-2) | | 9x+10y=3660 | | -9y-11=12 | | 0=-10-5X^2-27X | | 72+4x= | | 64x^2-2x+1= | | 10k^2=-12 | | 32=32c | | 19-50x= | | c=15385+85 | | p=-10x^2+750x+-9000 | | -4+20=36 | | 10=2x-20 | | 3x-6(-1/3+8)=-3 | | X(X-16)-63=0 | | 2x+6x-80=112 |

Equations solver categories